Correct use of masks during the Covid-19 pandemic in Beringin Village, Barito Kuala - Muthmainnah muthmainnah (Borneo Community Development, 2021)
Covid-19 began with the first reports of an outbreak that occurred in the city of Wuhan, China. Symptoms include fever, malaise, dry cough and dyspnea. This disease is caused by the SARS-CoV-2 virus, also known as the coronavirus that causes outbreaks of Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS). Community Service Activities will be held in August 2021. The first stage before community service is carried out is observing problems that occur in the banyan village. The second stage is activity planning and the third stage is activity implementation. . This activity is carried out to the public to get used to wearing masks properly. The correct use of masks is that the mask must be used properly from the chin to cover the mouth and nose on the left and right of the face. The high incidence of Covid-19 in Indonesia, so to reduce the bad impact it is necessary to explain the use of masks correctly to minimize the spread of Covid-19